Beamline K11 DIAD: a new instrument for dual imaging and diffraction at Diamond Light Source. (22nd October 2021) - Reinhard, Christina; Drakopoulos, Michael; Ahmed, Sharif I.; Deyhle, Hans; James, Andrew; Charlesworth, Christopher M.; Burt, Martin; Sutter, John; Alexander, Steven; Garland, Peter; Yates, Thomas; Marshall, Russell; et al.
Abstract : This manuscript summarizes the capabilities of the new DIAD beamline for dual imaging and diffraction (DIAD) at Diamond Light Source, dedicated to quasi‐simultaneous, time‐resolved imaging/tomography and powder diffraction for 3D microstructure and phase identification/strain analysis studies. Abstract : The Dual Imaging and Diffraction (DIAD) beamline at Diamond Light Source is a new dual‐beam instrument for full‐field imaging/tomography and powder diffraction. This instrument provides the user community with the capability to dynamically image 2D and 3D complex structures and perform phase identification and/or strain mapping using micro‐diffraction. The aim is to enable in situ and in operando experiments that require spatially correlated results from both techniques, by providing measurements from the same specimen location quasi‐simultaneously. Using an unusual optical layout, DIAD has two independent beams originating from one source that operate in the medium energy range (7–38 keV) and are combined at one sample position. Here, either radiography or tomography can be performed using monochromatic or pink beam, with a 1.4 mm × 1.2 mm field of view and a feature resolution of 1.2 µm. Micro‐diffraction is possible with a variable beam size between 13 µm × 4 µm and 50 µm × 50 µm. One key functionality of the beamline is image‐guided diffraction, a setup in which the micro‐diffraction beam can be scanned over the complete area of the imaging field‐of‐view. This moving beam setup enables the collection of location‐specific information about the phase composition and/or strains at any given position within the image/tomography field of view. The dual beam design allows fast switching between imaging and diffraction mode without the need of complicated and time‐consuming mode switches. Real‐time selection of areas of interest for diffraction measurements as well as the simultaneous collection of both imaging and diffraction data of (irreversible) in situ and in operando experiments are possible.